Journal of the International Society of Sports Nutrition - Kalman, Douglas; Antonio, Jose; Kreider, Richard
Journal of the International Society of Sports Nutrition (JISSN) focuses on the acute and chronic effects of sports nutrition and supplementation strategies on body composition, physical performance and metabolism. JISSN is aimed at researchers and sport enthusiasts focused on delivering knowledge on exercise and nutrition on health, disease, rehabilitation, training, and performance. The journal provides a platform on which readers can determine nutritional strategies that may enhance exercise and/or training adaptations leading to improved health and performance.